PEMANFAATAN ASAP CAIR DAN MINYAK BIJI MIMBA SEBAGAI BIPOESTISIDA PENGENDALIAN HAMA WERENG BATANG COKLAT (NILAPARVATA LUGENS) - Ririn Suryani; Sujono Sujono; Arief Heru Prianto (Komunitas Menulis dan Meneliti (Kolibi), 2023)
Brown stems (Nilaparvata lugens) are pest nsects that are spread across Indonesia, China, Vietnam, Thailand, India, Pakistan, Malaysia, the Philippines, Japan and Korea. Brown stalks only attack one type of plant, that is rice plants by sucking fluid in the vascular system (plant vessels). One effort to control planthopper pests is by planting rice varieties resistant to brown plant hopper attacks and safe for the environment. Another effort that can be used to control brown plant hopper pests is by spraying biopesticides. Biopesticides used can be a mixture of neem seed oil, liquid smoke and surfactants (Rodacal and Gronol).In this study includes the preparation of materials in the form of rice husks for the manufacture of liquid smoke by pyrolysis process. Making a formulation of a mixture of liquid smoke, neem seed oil, rodacal and gronol. Tested phenol levels and acid levels in liquid rice husk smoke. For physical analysis of liquid smoke and neem seed oil include pH and specific gravity. This study uses a Completely Randomized Design with 7 types of treatment including control with 3 repetitions. The data analysis using ANOVA followed by a real difference test or commonly called the BNT 5% test. The fornmulation used in this study was Pl that the concentration of 30% for 30% neem seed oil, 60% liquid smoke, and 10% surfactants. P2 with concentration of 10% for 30% neem seed oil, 60% liquid smoke, and 10% surfactants. P3 with concentration of 30% for 25% neem seed oil, 75% liquid Smoke, and 10% surfactants. P4 with concentration of 10% for 25o neem seed oil, 75% liquid smoke, and 10% surfactants. P5 with concentration of 30% for 20% neem seed oil, 80% liquid smoke, and 10% surfactants. P6 with concentration of 10% for 20% neem seed oil, 80% liquid smoke, and 10% surfactants. The best formulation was obtained for the 6 formulations in the P1 formulation, which in this formulation has the highest content of neem seed oil among others.